Metode Gravity Location Models Dalam Penentuan Lokasi Cabang Yang Optimal Di PT. ABC - Elly Wuryaningtyas Yunitasari (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2015)
Implementation of Supply Chain strategy can only take place effectively if the Supply Chain has a network with the appropriate configuration. This means that the structure or network configuration can determine wheter a Supply Chain can be responsive or efficient. If want a responsive Supply Chain, the network configuration must be supported by production and warehouse facilities are more numerous and scattered in various locations marketing. Likewise, if the Supply Chain wants to efficiently then there is a relatively centralized network with fewer amenities. The purpose of this study is to obtain an optimal local warehouse position that minimizes transportation costs. Gravity location models used to determine the location or position of a facility (such as a warehouse or factory) which became a liaison between sources of supply and markets several locations. The steps in this research is to calculate the distance ji to all i (that is the location of the facility and the location of candidate sources of supply or market i), determine the coordinates of the location and when two successive iterations produce nearly the same coordinates, the iteration stops and select it as the location coordinates facilities. If not, repeat the iteration start step 1. Local warehouse optimal position that minimizes transportation costs are (0,04;0,07).